2002
DOI: 10.1007/bf03039993
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of monosodium glutamate use for enhancement of spinosad toxicity against codling moth neonates

Abstract: It was demonstrated that neonates of the codling moth, Cydia pomonella (L.), feed on 'Red Delicious' apple leaves and successfully molt to the second instar. Next, using a nonchoice bioassay, we targeted codling moth neonates feeding on apple leaves, with standard concentrations of a culinary taste enhancer, monosodium glutamate (MSG), and Success ® , which contains 22.8% spinosad as its active ingredient. The addition of 25 ppm MSG increased feeding by 20-30%. Stimulatory properties of MSG were preserved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…There is another explanation why stimulatory effect of MSG lasted for so long in obliquebanded leafrollers. As we have shown elsewhere ( Pszczolkowski and Brown , 2002), with time MSG residues on leaves tend to loose their stimulatory properties after 7 days. In our present study we used about 10 times higher dose of MSG than the minimum stimulatory dose both for the codling moth ( Pszczolkowski et al., 2002) and for obliquebanded leafroller (this study).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…There is another explanation why stimulatory effect of MSG lasted for so long in obliquebanded leafrollers. As we have shown elsewhere ( Pszczolkowski and Brown , 2002), with time MSG residues on leaves tend to loose their stimulatory properties after 7 days. In our present study we used about 10 times higher dose of MSG than the minimum stimulatory dose both for the codling moth ( Pszczolkowski et al., 2002) and for obliquebanded leafroller (this study).…”
Section: Discussionsupporting
confidence: 74%
“…Our data showed that MSG stimulates feeding of obliquebanded leafroller within a broad range of concentrations 50–700 μ g/l. The obliquebanded leafroller responds to MSG by increasing leaf tissue consumption at 50 μ g/l concentration, which resembles the minimum effective MSG concentrations that stimulate feeding in the codling moth too ( Pszczolkowski and Brown , 2002; Pszczolkowski et al., 2002). This fact suggests that threshold MSG concentrations are similar in neonates of the obligueband leafroller and the codling moth.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Most the microscope slides were kept in Petri dishes with wet fi lter paper placed on the bottom of each dish. Additional details of this procedure are given elsewhere (Pszczolkowski & Brown, 2002).…”
Section: Introductionmentioning
confidence: 99%